2023
DOI: 10.3390/app13137813
|View full text |Cite
|
Sign up to set email alerts
|

Using Imaging Techniques to Analyze the Microstructure of Asphalt Concrete Mixtures: Literature Review

Abstract: The performance of asphalt concrete (AC) mixtures depends highly on their internal structure and the interaction of the mixture components under different loading conditions. Imaging techniques provide effective tools that can assess the microstructure and failure mechanisms of materials. Imaging techniques have been used in recent research studies to examine and analyze the evolution of the internal structure of AC mixtures resulting from traffic and environmental loading. Increasing knowledge of the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…One of the recorded images is defined as the reference image for all subsequent analyses. Software using DIC analyzes changes in the position of each point registered on the reference image, over the entire load range [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The DIC analysis results in displacement values from which, in the next step, strains are determined from simple relationships.…”
Section: Methodsmentioning
confidence: 99%
“…One of the recorded images is defined as the reference image for all subsequent analyses. Software using DIC analyzes changes in the position of each point registered on the reference image, over the entire load range [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The DIC analysis results in displacement values from which, in the next step, strains are determined from simple relationships.…”
Section: Methodsmentioning
confidence: 99%
“…One of them is to create a virtual/synthetic microstructure that possesses selected properties (e.g., the gradation curve and weight ratio) of the real material. A group of studies using this approach can be found in the literature [3][4][5][6][7][8][9]. Apparently, they may be considered as over-simplifying the real AC microstructure, thus are rather impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Their results are of particular importance for the material model validation and calibration. A comprehensive review of these three methods is presented in [3]. Therein, the application limits of each of them are specified, to mention only one of the discussed aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in non-destructive testing techniques have paved the way for novel approaches to studying the evolution of air voids within AC. Recently, X-ray computed tomography (CT) scanning has emerged as a powerful and non-invasive tool to capture intricate details of the internal structure of AC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%